PENGARUH CUSTOMER SERVICE STRATEGIES TERHADAP AMAZING CUSTOMER EXPERIENCES MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI - Muntasir, Muhammad Saifuddin; Wahyuni, Sri; Totalia, Salman Alfarisy (Department of Economics Education, Universitas Sebelas Maret, 2016)
The aims of this research are: (1) to know the effect of the customer service strategies consisting of membership, serious fun, partnership, hire right, after-experience, community, and walk the walk toward the amazing customer experiences in students of Economic Education Study Program; (2) to know the effect of the membership toward the amazing customer experiences in students of economic education study program; (3) to know the effect of the serious fun toward the amazing customer experiences in students of Economic Education Study Program; (4) to know the effect of the partnership toward the amazing customer experiences in students of Economic Education Study Program; (5) to know the effect of the hire right toward the amazing customer experiences in students of Economic Education Study Program; (6) to know the effect of the after-experience toward the amazing customer experiences in students of Economic Education Study Program; (7) to know the effect of the community toward the amazing customer experiences in students of Economic Education Study Program; (8) to know the effect of the walk the walk toward the amazing customer experiences in students of Economic Education Study Program. The research is descriptive quantitative. The population of the research were all of students of Economic Education Study Program in 2013-2015 with the total number of 187 student. The samples of the research were 127 student by using proportionate sratified random sampling. The data were obtained by questioners. The data were analyzed by using double regression, F test and T test. The results of this research show: (1) there is an positive effect of the customer service strategies consisting of membership, serious fun, partnership, hire right, after-experience, community, and walk the walk toward the amazing customer experiences in students of Economic Education Study Program; (2) there is an positive effect of the membership toward the amazing customer experiences in students of Economic Education Study Program; (3) there is an negative effect of the serious fun toward the amazing customer experiences in students of Economic Education Study Program; (4) there is an negative effect of the partnership toward the amazing customer experiences in students of Economic Education Study Program; (5) there is an negative effect of the hire right toward the amazing customer experiences in students of Economic Education Study Program; (6) there is an positive effect of the after-experience toward the amazing customer experiences in students of Economic Education Study Program; (7) there is an positive effect of the community toward the amazing customer experiences in students of Economic Education Study; (8) there is an positive effect of the walk the walk toward the amazing customer experiences in students of Economic Education Study Program.